A Improving Supply Chain Performance using the Supply Chain Operation Reference Digital Standard (SCOR DS) V14.0 Racetrack Model at PT Cipta Krida Bahari Kalimantan Area. - Tetelepta, Jerry; Ulfi Pristiana; Prastiwi, Estik Hari (International Journal of Economics (IJEC), 2025)
The purpose of this study is to improve the supply chain performance of PT Cipta Krida Bahari (CKB) in the Kalimantan area by applying the Supply Chain Operation Reference Digital Standard (SCOR DS) version 14.0 Racetrack model, with a particular focus on solving issues related to reliability and asset utilization. This study employed a quantitative descriptive method using a case study approach. Primary data were collected through direct observation, structured interviews with key supply chain managers, and an analysis of internal company reports. The SCOR DS v14.0 Racetrack model was used as a framework for diagnosing performance gaps and identifying targeted improvements across key attributes in five stages: engaging, defining, analyzing, planning, and launching. Performance measurement is carried out starting from level-2 then down to level-3 performance metrics. The results in level-2 performance metrics belonging to reliability show that there is one metric that does not meet the 100% target, namely RL.2.2, delivery performance to the original customer commit date of 89.94%. In level-3 performance metrics, of the two metrics, there is one metric that has gaps, namely RL.3.3 customer commit date achievement of 5.06%. With these gaps, the implications of this research suggest for improvement projects referring to the best practices in the SCOR guide, namely BP.017 Distribution Planning, BP.042 Procurement Terms & Conditions Review, BP.055 Freight Carrier Delivery Performance Evaluation, and Regular Reconciliation Meetings. This study contributes a novel application of SCOR DS v14.0 Racetrack in a logistics and freight forwarding company context, where the model has been rarely implemented, especially in emerging markets. It also provides a replicable case study for improving service reliability in complex geographical regions such as Kalimantan, Indonesia